A study on the current situation and countermeasures for the development of outdoor education in schools in Jiangxi Province, China - Xiaoming, Yang; Yubin, Yuan; Samsudin, Shamsulariffin (ASR Research Center, 2022)
Outdoor education is an emerging sport in China in recent years. The reason why it is favored by the majority of primary and secondary school is that outdoor education enthusiasts, who are able to participate in various types of outdoor sports activities. On the one hand, outdoor education can significantly improve one's physical education and sports literacy, on the other hand, it can cultivate moral sentiment, cultivate the body and exercise the body, etc. At the same time, China's curriculum reform has put forward higher requirements for outdoor education teaching, highlighting the main position of students in the practice of outdoor sports, in line with the requirements of physical health education teaching. Jiangxi Province has made great efforts in recent years to promote and popularize the importance of the outdoor education movement and to promote the quality and level of outdoor education in Jiangxi Province.This study addresses some of the problems revealed in the development process and proposes corresponding measures to cope with them, ultimately laying the foundation for the sustainable development of outdoor education.